A rare cause of back pain and radiculopathy - Spinal tophi: A case report - Wan, S.A; Teh, C.L; Jobli, A.T.; Cheong, Y.K; Chin, W.V.; Tan, B.B. (BioMed Central Ltd., 2019)
Background: Gout is a monosodium urate deposition disease which is prevalent worldwide. The usual manifestations are crystal arthropathy and tophi deposition in the soft tissues. Spinal tophi may also occur and are rarely reported, resulting in various clinical manifestations such as back pain, spinal cord compression, radiculopathy, and even mimicking epidural abscess and spondylodiscitis. Case presentation: We report a case of a 42-year-old Chinese man with underlying gout who presented with back pain and radiculopathy. The diagnosis of spinal tophi was unsuspected and he was initially treated for epidural abscess and spondylodiscitis. He underwent a laminectomy and posterolateral fusion during which tophus material was discovered. He recovered and medications for gout were started. Conclusion: Spinal tophi are rare. The diagnosis is difficult and spinal tophi may be mistaken for epidural abscess, spondylodiscitis, or neoplasm. © 2019 The Author(s).